2017
DOI: 10.1111/jpc.13778
|View full text |Cite
|
Sign up to set email alerts
|

Management of Shiga toxin producing Escherichia coli‐infected children: A multi‐national, multi‐specialty survey

Abstract: Compared with paediatric nephrologists, paediatric emergency medicine physicians are less likely to perform baseline and follow-up blood tests and to administer intravascular volume expansion in children at risk of, and with confirmed, E. coli O157:H7 infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
(37 reference statements)
0
6
0
1
Order By: Relevance
“…The lack of recognition of STEC infections might have contributed to underuse this strategy; nevertheless, no patient with early pathogen identification received this treatment, raising the possibility that providers hesitated to give fluids to children at risk of impending renal failure or that they were not aware that intravenous volume expansion is warranted for these infections. Supporting this, a multinational survey conducted in the United States and Canada indicated that pediatric emergency physicians recommend intravenous fluids in this setting less frequently than do nephrologists 30 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of recognition of STEC infections might have contributed to underuse this strategy; nevertheless, no patient with early pathogen identification received this treatment, raising the possibility that providers hesitated to give fluids to children at risk of impending renal failure or that they were not aware that intravenous volume expansion is warranted for these infections. Supporting this, a multinational survey conducted in the United States and Canada indicated that pediatric emergency physicians recommend intravenous fluids in this setting less frequently than do nephrologists 30 …”
Section: Discussionmentioning
confidence: 99%
“…Supporting this, a multinational survey conducted in the United States and Canada indicated that pediatric emergency physicians recommend intravenous fluids in this setting less frequently than do nephrologists. 30 A strength of this investigation is the large cohort analyzed unbiased by outbreak situations. The long period of time studied also provides information on change management over time.…”
Section: Discussionmentioning
confidence: 99%
“…The general medical community remain inadequately informed of the risks of developing HUS following an enteric infection with STEC organisms. This was highlighted in a recent study which showed that emergency physicians responded in a different manner to children diagnosed with a STEC infection when compared with paediatric nephrologists [28]. Improved education of primary and secondary healthcare workers may help in early recognition and the initiation of appropriate treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Hyponatremia is related to CNS complications, such as seizures and encephalopathy, and is also a strong predictor of death risk in D+HUS patients. [24][25][26][27] In our study, the initial hyponatremia was corrected in 24 hours, and blood sodium was kept within normal ranges in the VE group. After 48 hours, the number of patients with hyponatremia was statistically and significantly higher in the FR group (p = 0.014).…”
Section: Diarrhea-associated Hemolytic Uremic Syndrome and Hyponatremiamentioning
confidence: 91%